ANALYSIS OF SUBSURFACE STRUCTURE OF IRON SAND POTENTIAL WITH 3D MODELLING RESISTIVITY GEOELECTRIC METHOD IN PANDANWANGI VILLAGE KUNIR LUMAJANG - Ubaidillah, Mahrul Junaid; Anggraeni, Firdha Kusuma Ayu; Prihandono, Trapsilo Prihandono (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2024)
This research was conducted to analyze the sub-surface structure of the potential iron sand area and the distribution of iron sand depth in terms of its specific resistivity in Pandanwangi Village, Kunir District, Lumajang Regency. This research uses the Wenner configuration resistivity geoelectric method to identify subsurface structures. Measurements were made using 4 lines that have a length of 200 meters per line and then processed using Res2Dinv software to see the results of the 2D cross-section and using Voxler software to see the results of the 3D cross-section. Based on the results of the study, there are several types of rocks and constituent minerals that are below the ground surface, including iron sand, sand, sandstone, and basalt which are found at certain depths. Line 1 tends to contain sand, and line 2 is often passed by residents' vehicles so that it has a different density than other lines because, on line 3, activities are often carried out by local residents. Line 3 has the least iron sand potential compared to other lines, and line 4 has the greatest iron sand potential than other lines. The potential of iron sand is assessed based on its lower resistivity value compared to other rocks and minerals, which is around 0.13-37.11 Ωm.